Dual‐layered hydrogels allow complete genome recovery with nucleic acid cytometry. Issue 4 (10th February 2022) - Hatori, Makiko N.; Modavi, Cyrus; Xu, Peng; Weisgerber, Daniel; Abate, Adam R.
Abstract: Targeting specific cells for sequencing is important for applications in cancer, microbiology, and infectious disease. Nucleic acid cytometry (NAC) is a powerful approach for accomplishing this because it allows specific cells to be isolated based on sequence biomarkers that are otherwise impossible to detect. However, existing methods require specialized microfluidic devices, limiting adoption. Here, a modified workflow is described that uses particle‐templated emulsification (PTE) and flow cytometry to conduct the essential steps of cell detection and sorting normally accomplished by microfluidics. Our microfluidic‐free workflow allows facile isolation and sequencing of cells, viruses, and nucleic acids and thus provides a powerful enrichment approach for targeted sequencing applications. Graphical Abstract and Lay Summary: Targeting specific cells for sequencing is important when studying sub‐populations. A method was developed to enrich the genomes of target sub‐populations from a sample using microfluidic‐free PCR‐activated cell sorting; the entire process consists of bulk mixing steps followed by commercial fluorescence‐activated sorting for the enrichment. Removal of specialized microfluidics increases accessibility to non‐expert labs.